Application of Digital Books through Guided Discovery Learning to Improve Mathematical Problem Solving Ability of Class VIII Students at SMP Swasta Dharma Patra - Mutiara Khadijah; Ani Minarni (Asian Journal of Applied Education (AJAE), 2023)
The purpose of this study was (1) to find out whether the application of digital books through Guided Discovery Learning in class VIII of SMP Swasta Dharma Patra could improve mathematical problem-solving ability and (2) to determine the improvement of students' mathematical problem-solving ability by applying digital books through Guided Discovery Learning in class VIII of SMP Swasta Dharma Patra for the 2022/2023 academic year. The subjects were 37 students of class VIII-A SMP Swasta Dharma Patra. Data collection techniques used are teacher observation sheets, mathematical problem-solving ability tests, and documentation. Researcher used type of classroom action research (CAR). Preliminary tests result obtained 6 students (17.14%) completed with an average of 50.91% (lower). In the tests cycle I, 19 students (51.35%) completed with an average of 68,75% (low). In the test cycle II, 36 students (97%) were completed with an average of 85% (high). It can be concluded that the application of digital books through guided discovery learning can improve the mathematical problem-solving ability of VIII students at SMP Swasta Dharma Patra